A DESCRIPTIVE ANALYSIS OF ARGUMENTATIVE DISCOURSE PERFORMED BY DEBATERS IN ENGLISH EDUCATION DEPARTMENT ENGLISH DEBATING CHAMPIONSHIP 2014 - ., Ria Rarasati; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., I Nyoman Pasek Hadi Saputra, S.Pd., M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This study attempted to analyze the structure of arguments produced by debaters in debating using Asian Parliamentary System performed by debaters in English Education Department English Debating Championship 2014 and how the debaters fulfilled the elements of reasonable arguments. The data were collected through video recording and non-participatory observations, while the process of data analysis was done in accordance with van Eemeren’s structure of argumentative discourse (1984) and Toulmin’s elements of reasonable argument (1958). The subjects of this study were ten (10) debaters that performed in the competition. This research revealed that the subjects of this study showed the use of argumentative discourse as well as present reasonable arguments in their performances. The data collected were grouped and analyzed based on van Eemeren’s structure of argumentative discourse (1984) namely; confrontation, opening, argumentation, and concluding stage. Furthermore, the data were also analyzed by using Toulmin’s elements of reasonable argument (1958) which consists of Claim (C), Data (D), Warrant (W), Qualifier (Q), Backing (B), and Rebuttal (R). The result of the research showed that only six of ten debaters were able to fulfill the criteria of good argument based on van Eemeren and Toulmin’s theory. keyword : arguments, structure, reasonableness, debaters